1990
DOI: 10.1111/j.1365-3040.1990.tb01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in starch and soluble sugars in relation to the acquisition of desiccation tolerance during maturation of Brassica campestris seed

Abstract: Abstract. We investigated the onset of desiccation tolerance in developing embryos of Brassica campestris seeds and possible correlated ultrastructural modifications in the radiele cells. Since the acquisition of desiccation tolerance is a long asynchronous process which took 9 d to be achieved, we determined criteria allowing us to separate freshly intact harvested seeds into desiccation intolerant and desication tolerant batches that differed in age by only 2 d. No particular structural modifications were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
1
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 19 publications
2
57
1
3
Order By: Relevance
“…The precise causes that trigger the metabolic arrest during drying are not known. Electron microscopy studies have suggested that the progressive shutdown of metabolism is associated with a general dedifferentiation of organelles (Leprince et al, 1990; for review, see Vertucci and Farrant, 1995). In cowpea we observed a biphasic pattern in the relation between viscosity and respiration.…”
Section: A Functional Role For Cytoplasmic Viscosity In Depressing Mementioning
confidence: 68%
See 1 more Smart Citation
“…The precise causes that trigger the metabolic arrest during drying are not known. Electron microscopy studies have suggested that the progressive shutdown of metabolism is associated with a general dedifferentiation of organelles (Leprince et al, 1990; for review, see Vertucci and Farrant, 1995). In cowpea we observed a biphasic pattern in the relation between viscosity and respiration.…”
Section: A Functional Role For Cytoplasmic Viscosity In Depressing Mementioning
confidence: 68%
“…Two mechanisms of protection against the deleterious effects of water loss have received major attention: (a) the synthesis of the so-called lateembryogenesis-abundant proteins (Close, 1996;Kermode, 1997) and (b) the accumulation of di-and oligosaccharides (Leprince et al, 1990;Horbowicz and Obendorf, 1994;Vertucci and Farrant, 1995). In model systems these sugars protect the structural integrity of dehydrated membranes and proteins (Crowe et al, 1992;Hoekstra et al, 1997).…”
mentioning
confidence: 99%
“…Trehalose has been shown to be a particularly effective protectant in anhydrobiotic organisms such as yeast, nematodes, fungi, and bacteria, whereas in seeds and pollen, Suc appears to play the same role (Crowe et al, 1992). Many orthodox seeds accumulate high amounts of Suc and oligosaccharides during maturation (Amuti and Pollard, 1977), and sugar accumulation has been correlated with an increase in desiccation tolerance (Leprince et al, 1990;Blackman et al, 1992). Oligosaccharides have been proposed to inhibit Suc crystallization, a situation that is favored by slow drying (Koster and Leopold, 1988), and may be involved in desiccation tolerance by promoting glass formation at water contents 4 0 % (Bruni and Leopold, 1991).…”
mentioning
confidence: 99%
“…Many of the bryophytes are highly desiccation-tolerant, so their carbohydrate composition is of interest. High sucrose concentration has been suggested as a prerequisite for desiccation tolerance in seeds and pollen (Koster & Leopold, 1988 ;Leprince, Bronchart & Deltour, 1990) and in the desiccationtolerant leaves of angiosperm ' resurrection ' plants (Ingrams & Bartels, 1996). By contrast, the desiccation tolerance of the pteridophyte Selaginella lepidophylla, of fungal spores and of desiccationtolerant invertebrates is associated with the di-saccharide trehalose (Ingram & Bartels, 1996).…”
mentioning
confidence: 99%